2020
DOI: 10.1101/2020.09.21.304196
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multivariate GWAS elucidates the genetic architecture of alcohol consumption and misuse, corrects biases, and reveals novel associations with disease

Abstract: Genome-wide association studies (GWASs) of the Alcohol Use Disorder Identification Test (AUDIT), a ten-item screener for alcohol use disorder (AUD), have elucidated novel loci for alcohol consumption and misuse. However, these studies also revealed that GWASs can be influenced by numerous biases (e.g., measurement error, selection bias), which have led to inconsistent genetic correlations between alcohol involvement and AUD, as well as paradoxically negative genetic correlations between alcohol involvement and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…For all UK Biobank traits, we limited our sample to only current drinkers, to reduce misreporting and longitudinal bias. We excluded AUDIT items 6 and 9 as they both had low SNP-heritabilities (-Table S2), similar to Mallard, Savage, et al (2020). Chang et al, 2015, command: --maf 0.01 -hwe 1e-8 -indep-pairwise 50 5 0.2), which also (using the same quality control, but without LD-pruning) were used in BOLT-LMM to control for relatedness.…”
Section: Study Samples and Phenotypesmentioning
confidence: 99%
See 4 more Smart Citations
“…For all UK Biobank traits, we limited our sample to only current drinkers, to reduce misreporting and longitudinal bias. We excluded AUDIT items 6 and 9 as they both had low SNP-heritabilities (-Table S2), similar to Mallard, Savage, et al (2020). Chang et al, 2015, command: --maf 0.01 -hwe 1e-8 -indep-pairwise 50 5 0.2), which also (using the same quality control, but without LD-pruning) were used in BOLT-LMM to control for relatedness.…”
Section: Study Samples and Phenotypesmentioning
confidence: 99%
“…We modeled the genetic correlation matrix using a confirmatory factor analysis with four latent factors based on prior knowledge of the alcohol and internalizing phenotypes (K. S. Kendler, Aggen, Prescott, Crabbe, & Neale, 2012;Mallard, Savage, et al, 2020;Polimanti et al, 2019;Sanchez-Roige et al, 2019), as well as the patterns identified in the genetic correlation matrix. We chose to use confirmatory factor analysis, as opposed to exploratory factor analysis, to validate tests can be used to compare nested models (Hu & Bentler, 1998).…”
Section: Genomic Structural Equation Modeling and Multivariate Gwasmentioning
confidence: 99%
See 3 more Smart Citations